Construction of CRISPR/Cas9 vector for editing IaVQ9 gene in Ipomoea aquatica - Hue, Huynh Thi Thu; Ngoc, Nguyen Thi Bich; Thanh , Le Tat; Hoa, Nguyen Thi; Tri , Le Minh; Thuy, Le Thi Bich (Vietnam Journal of Biotechnology, 2024)
The group of proteins containing the VQ motif (named VQ proteins) is a family of plant-specific proteins with a FxxhVQxhTG conservative VQ-motif region. VQ proteins regulate many developmental processes, including responses to biotic and abiotic stresses, and seed development. The VQ9 protein has an interaction with the WRKY8 factor, when this interaction occurs, it causes a decrease in the DNA binding ability of WRKY8 to DNA, which plays a role in the regulation function of the plant to stress. Some mutations in the VQ9 gene increase salt tolerance in plants, suggesting that VQ9 acts antagonistically to regulate responses to salt conditions. This antagonism is consistent with an increase or decrease in the Na+/K+ ratio. Ipomoea aquatica is commonly grown and used as a vegetable in Southeast Asia. The research involved RNA extraction from I. aquatica leaves, followed by PCR sequencing to confirm the presence of the IaVQ9 gene. Subsequently, a specific guide RNA (gRNA) was designed using CRISPR-P ver.2.0 and inserted into the pRGEB31 vector, optimized for CRISPR/Cas9 applications. The gRNA-inserted vector was successfully transformed into E. coli DH10B and then into Agrobacterium tumefaciens EHA105, verified through colony PCR and restriction enzyme analysis. This process created a delivery system capable of editing the VQ9 gene in I. aquatica. This research represents a significant step towards improving crop resilience to salinity, addressing a critical challenge for agriculture in salt-affected regions. Future studies will focus on transferring the construct back into I. aquatica plants to assess its impact on enhancing salt tolerance, potentially contributing to sustainable crop production in adverse environmental conditions.